Overstory and understory vegetation interact to alter soil community composition and activity - Mitchell, Ruth Joy; Keith, Adian M.; Potts, Jackie M.; Ross, Jasmine; Reid, Eileen; Dawson, Lorna A. (Plant and soil, 2012)
Aim To test if there is an interactive effect between tree and understory species on the soil microbial community (SMC), community level physiological profiles (CLPP) and soil micro-fauna. Method A replicate pot experiment with five sapling tree species (Betula pendula, Betula pubescens, Sorbus aucuparia, Quercus petraea and Pinus sylvestris) and a no-tree treatment with and without Calluna vulgaris was established. After 21 months samples were taken for phospholipid fatty acid (PLFA) analysis, CLPP and soil microfauna assessment. Results There was an interactive effects of tree species and Calluna on the SMC, CLPP and nematode densities. Calluna addition changed the SMC composition (increase in fungal PLFAs) and the CLPP (lower utilisation of most carbon sources but greater utilisation of phenolic acids). A multivariate test for homogeneity of dispersion showed that while Calluna addition resulted in the presence of an altered microbial composition, it did not result in there being less variability among the samples with Calluna than among the samples without Calluna. Sapling trees with Calluna present grew less well than trees without Calluna. Structural equation modelling showed that it is possible that Calluna had an indirect effect on the SMC via below-ground tree biomass as well as a direct effect. Conclusion Interactions between trees and understory vegetation can impact on the composition of soil biota and their activity.